Histochemical and biochemical study of rabbit intestine in healthy and affected by epizootic enteropathy animals - XYLOURI (Ε. Μ. ΞΥΛΟΥΡΗ) E. M.; SABATAKOU (Ο. ΣΑΜΠΑΤΑΚΟΥ) O. A.; KALDRYMIDOU (Ε. ΚΑΛΔΡΥΜΙΔΟΥ) E.; SOTIRAKOGLOU (Α. Κ. ΣΩΤΗΡΑΚΟΓΛΟΥ) K. A.; FRAGKIADAKIS (Μ. Γ. ΦΡΑΓΚΙΑΔΑΚΗΣ) G. M.; NOIKOKYRIS (Π. Ν. ΝΟΙΚΟΚΥΡΗΣ) P. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Rabbits are suffering from Epizootic Rabbit Enteropathy (ERE), a new gastro-intestinal syndrome of unknown aetiology. ERE has not yet been investigated thoroughly from the patho-physiological point of view of the intestine malfunction during the intestine dysbiosis. For this reason, the aim of the present research was to study the haematological profile, the intestine histopathology and certain biochemical parameters (α-amylase activity, blood glucose concentration) of animals affected by ERE in comparison with those of healthy rabbits of the same age. In six healthy and six, affected by ERE, crossbreed New Zealand X California 35-day old rabbits, the following analyses were performed: Total blood count, histopathological morphology of the intestine, alkaline phosphatase (ALP) distribution in intestine brush border and α-amylase activity in blood plasma and small intestine epithelium, respectively. Total blood count showed significantly (at 95% confidence level) decreased values for all blood parameters except for the white blood cell count, which proved to be significantly higher compared in ERE rabbits to that of normal rabbits. The a-amylase activity and concentration in blood plasma and intestinal epithelium were significantly (a=0.05) decreased, in contrast to blood glucose concentration, that was found to be significantly increased in ERE rabbits. Stomach was full of watery content, intestine presented non-specific enteropathy and mainly the small intestine was full of gas and watery content. Caecal and colon presented impaction and mucus was present in the colon. The histopathological evaluation of the ileum, sacculus rotundus, caecum and colon presented, mainly, lamina propria mononuclear cell infiltration and swelling, vacuolation, flattening and denuding of the enterocytes as well as oedematous lymphoid tissues. Duodenum had necrotic villi and deep infiltration with mononuclear and polymorphonuclear cells, within the lamina propria. Also swelling, vacuolation, flattening, enterocytes denuding and oedematous lymphoid tissue were observed. Jejunum had no lesions. The caecum and the colon presented an ALP positive reaction along the brush border of the epithelial cells. The small intestine presented a positive reaction along the brush border of intestinal glands-upper part- cells only and the bases of a few of the villi.